Nanocrystal-based per-oral itraconazole delivery: Superior in vitro dissolution enhancement versus Sporanox® is not realized in in vivo drug absorption - Sarnes, Annika; Kovalainen, Miia; Häkkinen, Merja R.; Laaksonen, Timo; Laru, Johanna; Kiesvaara, Juha; Ilkka, Jukka; Oksala, Olli; Rönkkö, Seppo; Järvinen, Kristiina; Hirvonen, Jouni; Peltonen, Leena (Journal of controlled release, 2014)
Nanoscience holds true promise in enabling efficient formulation development and in vivo delivery of poorly water soluble drugs. The objective of this study was to formulate solid oral nanocrystal delivery systems of itraconazole, and thus enhance the oral bioavailability of the very poorly soluble drug. Nanocrystal suspensions were prepared by a rapid wet milling technique, after which the suspensions were transformed into solid dosage forms by both freeze drying and granulating. Finally, the obtained nanocrystalline powders were capsule-packed as well as compacted to tablets. After in vitro analysis, the formulations (nanocrystal suspension (NPs), freeze dried NPs, granulated NPs) were tested in vivo in a rat model, and compared with commercial itraconazole formulation (Sporanox). Importantly, the results indicated rapid dissolution of the nanocrystalline itraconazole with enhanced bioavailability compared to physical mixture. Drug dissolution in vitro was immediate from NPs and freeze dried powder, and differed significantly from the marketed product (P=0.004 and 0.002, correspondingly) until 30min. Freeze drying was detected to be especially advantageous for the solid dosage forms. It is possible to maintain the original character of the nanocrystals, e.g. rapid dissolution, even after tableting of the nanocrystalline powders. Interestingly, the marketed product out-performed the nanocrystalline formulations in vivo, even though the nanocrystals provided reasonable bioavailability of itraconazole absorption as well. The efficient in vitro dissolution enhancement of the nanocrystalline formulations compared to Sporanox® was not realized in in vivo drug absorption. [Display omitted]